The Influence of Social Media Networks on Families Dynamics: Opportunities and Challenges - Khalili, Barge Gul; Qargha, Rahima; Quraishi, Tamanna (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2024)
Social media has become deeply entrenched in contemporary society, impacting family dynamics and communication. This study delves into how faculty members and students perceive and engage with social media within family settings across diverse academic disciplines and age groups. Understanding these perceptions is crucial for comprehending its impact on family relationships, privacy, and communication patterns. The research aims to uncover insights into the positive and negative effects of social media on families and assess the likelihood of leveraging it to strengthen familial bonds. Through a stratified sampling method, 160 participants were selected, and data was collected via a structured questionnaire distributed electronically. Analysis using SPSS and Excel revealed nuanced perspectives, with participants expressing concerns about privacy breaches, negative impacts, and communication breakdowns. The findings underscore the intricate interplay between social media and family dynamics, emphasizing the need for a balanced understanding of its effects. By acknowledging both challenges and opportunities, families can navigate the digital landscape more effectively, fostering positive communication and strengthening familial bonds.